Shifting National Holiday Times In the Context of the Labor Law System - Fajrian Noor Anugrah (PT ARRUS Intelektual Indonesia, 2023)
In the world of labor today, companies often shift national holiday time for power efficiency, but the rule that working on official holidays must be counted as overtime creates two different perceptions of the shift. The company applies national holidays to weekdays so that the company considers it normal work, but workers see it as a shift. Normative research analyzes laws and regulations. This research inventories and analyzes legislation on adjusting national holiday time in Indonesia's labor law system to determine workers' rights and obligations on government-set holidays and the legal basis for doing so. The study found that employers can order workers to work on government-set public holidays if they meet certain conditions and obligations based on statutory provisions, employment agreements, or collective labor agreements, which are supervised by the government, in this case the Ministry of Manpower, by imposing administrative and criminal penalties. provided that it meets the law and its implementing rules and work agreements or collective bargaining agreements pertaining to the nature and type of labor and the responsibility for Employers to pay overtime compensation for work on public holidays to Laborers.